2013
DOI: 10.1212/wnl.0b013e31828ab2c9
|View full text |Cite
|
Sign up to set email alerts
|

Screening for predementia AD

Abstract: Objective: Data from the Einstein Aging Study (EAS) were used to prospectively evaluate the free recall score from the Free and Cued Selective Reminding Test (FCSRT-FR) and Logical Memory I immediate recall (LM-IR) subtest of the Wechsler Memory Scale-Revised for prediction of incident Alzheimer disease (AD) dementia among individuals from a community-based cohort with memory complaints.Methods: Analyses included 854 participants, age $70 years, who initially had no dementia, and had memory complaints. Clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
97
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 24 publications
1
97
1
Order By: Relevance
“…Separation of the Aβ+ group based on CDR progression revealed that Aβ-related PACC decline is predominantly driven by the subset of Aβ+ that progress on the CDR. This is not surprising, given that the selection of the PACC components was heavily influenced by studies examining decline associated with progression to MCI and dementia [3335]. Although this finding provides confidence that PACC decline is associated with clinically relevant functional decline, it also suggests that PACC decline is honed for change that occurs relatively late in preclinical AD.…”
Section: Discussionmentioning
confidence: 99%
“…Separation of the Aβ+ group based on CDR progression revealed that Aβ-related PACC decline is predominantly driven by the subset of Aβ+ that progress on the CDR. This is not surprising, given that the selection of the PACC components was heavily influenced by studies examining decline associated with progression to MCI and dementia [3335]. Although this finding provides confidence that PACC decline is associated with clinically relevant functional decline, it also suggests that PACC decline is honed for change that occurs relatively late in preclinical AD.…”
Section: Discussionmentioning
confidence: 99%
“…Derby et al (2013) applied time-dependent ROC analyses in the investigation of progression to AD dementia using data from the Einstein Aging Study (EAS), where they studied the predictive ability of a few cognitive measures and they assumed proportional hazards model for these measures. In our work, we considered measures from CSF and neuroimaging domains in addition to the cognitive domain and we found that additional measures did improve on the predictive utility of the cognitive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 1921 have reported evidence that both list learning and paragraph recall (measures of episodic memory) tend to decline 7 to 10 years prior to the diagnosis of MCI or Alzheimer dementia. Recent data from amyloid imaging studies 2529 have reported a decline in multiple cognitive domains looking retrospectively at cognitive trajectories over 8 to 10 years prior to PET amyloid imaging 2224 and prospectively over 1- to 3-year longitudinal follow-up.…”
Section: Methodsmentioning
confidence: 99%